Analysis of Growth Phenology and Growth Rate of the Fragrant Olive (Osmanthus Fragrans) Plant - I. I., Zakriddinov; O. N., Abdulatifova (American Journal of Biology and Natural Sciences, 2025)
In this article, the growth cycle (phenology) and growth rate of the Osmanthus fragrans plant, which is famous for its ornamental, fragrant flowers and medicinal properties, were studied in the Namangan Regional University Scientific Research Laboratory and open soil experimental field. During the experiment, the plant's vegetation stages, calendar dates of leafing and flowering times, and monthly growth rates were monitored.